ETS1 and PAX5 transcription factors recruit AID to Igh DNA. Issue 10 (28th August 2018) - Grundström, Christine; Kumar, Anjani; Priya, Anshu; Negi, Neema; Grundström, Thomas
Abstract: B lymphocytes optimize antibody responses by class switch recombination (CSR), which changes the expressed constant region exon of the immunoglobulin heavy chain (IgH), and by somatic hypermutation (SH) that introduces point mutations in the variable regions of the antibody genes. Activation‐induced cytidine deaminase (AID) is the key mutagenic enzyme that initiates both these antibody diversification processes by deaminating cytosine to uracil. Here we asked the question if transcription factors can mediate the specific targeting of the antibody diversification by recruiting AID. We have recently reported that AID is together with the transcription factors E2A, PAX5 and IRF4 in a complex on key sequences of the Igh locus. Here we report that also ETS1 is together with AID in this complex on key sequences of the Igh locus in splenic B cells of mice. Furthermore, we show that both ETS1 and PAX5 can directly recruit AID to DNA sequences from the Igh locus with the specific binding site for the transcription factor. Taken together, our findings support the notion of a targeting mechanism for the selective diversification of antibody genes with limited genome wide mutagenesis by recruitment of AID by PAX5 and ETS1 in a transcription factor complex. Abstract : Activation‐induced cytidine deaminase (AID) that starts the processes of class switch recombination and somatic hypermutation is together with the transcription factors E2A, PAX5, ETS1, and IRF4 on key DNA sequences of the antibody heavy chain locus. Both ETS1 and PAX5 can directly recruit AID to DNA sequences from the locus.